ANALISIS PENGARUH PERSEPSI KEMANFAATAN, PERSEPSI KEMUDAHAN PENGGUNAAN, DAN KEPERCAYAAN TERHADAP MINAT MENGGUNAKAN ALAT PEMBAYARAN NON TUNAI DENGAN JAKONE MOBILE - Mitra Sami gultom; Nur Safitry (Ekonomi Islam, 2021)
This study aims to analyze how the effect of perceived usefulness, perceived ease of use and trust on interest in using non-cash payment instruments with jakone mobile on Bank DKI Syariah customers. The data used in this study is primary data and data collection using direct questionnaires with a sample of 100 people as respondents, this study uses probability sampling with simple random sampling method. The results of this study, in the t-test indicate that the perceived usefulness variable t-count value of 3.067 is greater than 1.98498, with a significant level value of t of 0.003 less than 0.05 which means that perceived usefulness has a positive effect on interest in using non-payment instruments. cash with jakone mobile. The ease of use variable t-count value of 7.498 is greater than 1.98498, with a significant level of t value of 0.000 less than 0.05 which means that the perception of ease of use has a positive effect on interest in using non-cash payment instruments with jakone mobile. The confidence variable t-count value is 2.679 which is greater than 1.98498, with a significant level of t value of 0.009 which is smaller than 0.05, which means that trust has a positive effect on interest in using non-cash payment instruments with jakone mobile. The results of the f test show that all independent variables consisting of perceived usefulness, perceived ease of use and trust simultaneously have a positive and significant effect on the dependent variable, namely interest in using non-cash payment instruments with jakone mobile, with an F count of 46.507 greater than 2.70 with significance level value of 0.000 is less than 0.05 Keywords: Perceived Usefulness, Perceived Ease of Use, Trust, Interest, JakOne Mobile